Does Brand Licensing Increase a Licensor's Shareholder Value? - ROBINSON, Adina B. (Institutional Knowledge at Singapore Management University, 2015)
This study examines 171 brand licensing announcements and subsequent changes in the licensor firms' shareholder values using the event study method. We find that although brand licensing announcements lead to positive abnormal returns on average, nearly 44% of the announcements in our sample are followed by negative abnormal returns. We argue that investors react more favorably to a brand licensing announcement when they believe (i) the brand has greater ability to stimulate licensee product sales (and thus generate higher royalties for the licensor) and (ii) the licensor firm has greater ability to limit licensee opportunism (and thus limit brand dilution and its adverse effect on sales of other products marketed under the brand name). In line with our hypotheses related to a brand's ability to stimulate licensee product sales, the study's findings suggest that investors react more favorably to announcements involving brands with greater brand fit and greater brand breadth. However, investors appear to react less favorably to announcements involving brands with higher advertising investments. In line with our hypotheses related to a licensor firm's ability to limit licensee opportunism, the study's findings suggest that investors react more favorably to announcements involving larger licensors; however, investors' reactions do not appear to be influenced by licensor firms' licensing experience.